Disrupting the “empathy machine”: The power and perils of virtual reality in addressing social issues - Sora-Domenjó, Carles (Frontiers in Psychology, 2022)
This article looks through a critical media lens at mediated effects and ethical concerns of virtual reality (VR) applications that explore personal and social issues through embodiment and storytelling. In recent years, the press, immersive media practitioners and researchers have promoted the potential of virtual reality storytelling to foster empathy. This research offers an interdisciplinary narrative review, with an evidence-based approach to challenge the assumptions that VR films elicit empathy in the participant – what I refer to as the VR-empathy model. A review of literature from the fields of psychology, computer science, embodiment, medicine, and virtual reality was carried out to question and counter these claims through case studies of both fiction and non-fiction VR experiences. The results reveal that there is little empirical evidence of a correlation between VR exposure and an increase in empathy that motivates pro-social behavior, and a lack of research covering VR films exposure eliciting empathy. Furthermore, the results show an alarming lack of research into the long-term effects of VR films and other VR immersive experiences. This contribution aims to understand and demystify the current “empathy machine” rhetoric and calls for more rigorous, scientific research that can authenticate future claims and systemize ethical best practices.